1977
DOI: 10.1346/ccmn.1977.0250306
|View full text |Cite
|
Sign up to set email alerts
|

Exchangeable Cation and Solvent Effects Upon the Interlamellar Environment of Smectites: Esr Spin Probe Studies

Abstract: Abstract--The ESR spin probe, TEMPAMINE +, was used to study the interlamellar behavior of adsorbed organic cations on hectorites solvated with water, ethanol, and water-ethanol mixtures, and saturated with several monovalent and divalent metallic cations. The mobility and orientation of the probe was affected greatly by the solvent, and to a lesser extent by the predominant exchangeable cation on the silicate surface. Most of the effects could be interpreted in terms of the basal spacings of the hectorite. In… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0

Year Published

1979
1979
1983
1983

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 7 publications
1
8
0
Order By: Relevance
“…Previous studies of TEMPAMINE + adsorbed on smectites solvated in ethanol and methanol have shown spectra attributable to highly oriented as well as nearly randomly tumbling species (McBride, 1976(McBride, , 1977a(McBride, , 1977b. The present study reveals that the former species predominates at very low adsorption levels, while the latter solutionlike species becomes more prevalent at higher levels ( Figure 6).…”
Section: Resultssupporting
confidence: 63%
See 4 more Smart Citations
“…Previous studies of TEMPAMINE + adsorbed on smectites solvated in ethanol and methanol have shown spectra attributable to highly oriented as well as nearly randomly tumbling species (McBride, 1976(McBride, , 1977a(McBride, , 1977b. The present study reveals that the former species predominates at very low adsorption levels, while the latter solutionlike species becomes more prevalent at higher levels ( Figure 6).…”
Section: Resultssupporting
confidence: 63%
“…The nature of the spectrum of the adsorbed probe has been discussed previously (McBride, 1976(McBride, , 1977a(McBride, , 1977b) and will not be described in detail here. However, an additional broad resonance centered on the Mt = 0 (middle) resonance of the TEMPAMINE + spectrum is evident at the 10% loading level, increasing in relative intensity to the 40% level, and finally decreasing again at the 100% level.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations